Perbandingan Metode Efron dan Breslow pada Regresi Cox Propotional Hazard yang Mengandung Ties - Sugito Mahendra Imran; La Ode Nashar; Nurwan Nurwan; Agusyarif Rezka Nuha (JOSTECH Journal of Science and Technology, 2023)
This study concerned to apply the Cox proportional hazard regression model to the incidence of ties using two approaches, namely the Efron approach and the Breslow approach, and find out its application in cases of dengue hemorrhagic fever at Dr. Hasri Ainun Habibie Hospital, Gorontalo Regency. Dengue hemorrhagic fever data was taken from Dr. Hasri Ainun Habibie Hospital, Gorontalo Regency. There were seven variables considered in this study, namely age, sex, Hemoglobin, Erythrocytes, Leukocytes, Platelets, and type of treatment. Then tested the proportional hazard assumption, all variables met the proportional hazard assumption and were included in the model. After testing the Cox best model, the two approaches used gave different results where there was one significant variable, namely, leukocytes in the Efron approach, while there was no single variable. significant based on the Breslow approach